Practical guidelines for automated peritoneal dialysis. - Suchai Sritippayawan (2018)
The development of APD technologies enables physician to customize PD treatment for optimal dialysis. Dialysis dose can be increased with APD alone or in conjunction with daytime dwells. Although there is no strong evidence of the advantage over CAPD, APD is generally recommended for patients having a high peritoneal transport, outflow problems or high intraperitoneal pressure (IPP) and those who depend on caregivers for their dialysis. The benefits of APD over CAPD depends on the problems and treatment results among dialysis centers. Before starting the APD, medical, psychosocial and financial aspects, catheter function, residual renal function (RRF), body surface area and peritoneal transport characteristic must be evaluated. The recommended starting prescription for APD is the dwell volume of 1,500 ml/m2, 2 hours/cycle, and 5 cycles/session, which will provides 10-15 L of total volume and 10 hours per session. The IPP should be monitored and kept below 18 cmH2O. NIPD is accepted for patients with significant RRF. Anuric patients usually require 15-20 L of total fill volume and may need 1-2 day-dwells of 2L icodextrin or hypertonic glucose solutions. Small solute clearances and ultrafiltration depend on the peritoneal catheter function and dialysis schedule. The clinical outcomes and small solute clearances must be monitored and adjusted accordingly to meet the weekly total Kt/V urea > or = 1.7 and in low peritoneal transporters, the weekly total CCr should be > or = 45 L/1.73 m2. The volume status must be normal. To diagnose the peritonitis in NIPD patients, 1 L of PDF should be infused and permitted to dwell for 2 hours before sending for analysis. The differential of white cell count may be more useful than the total cell counts. In Siriraj Hospital, APD patients had 1.5-3 times less peritonitis than CAPD patients and most of our anuric patients can achieve the weekly total Kt/V urea target with 10 L of NIPD.